Resurgent malaria at the millennium: control strategies in crisis. - Baird, J (2000)
Completion of the Panama Canal in 1914 marked the beginning of an era of vector control that achieved conspicuous success against malaria. In 1955 the World Health Organization (WHO) adopted the controversial Global Eradication Campaign emphasising DDT (dichlorodiphenyltrichloroethane) spraying in homes. The incidence of malaria fell sharply where the programme was implemented, but the strategy was not applied in holoendemic Africa. This, along with the failure to achieve eradication in larger tropical regions, contributed to disillusionment with the policy. The World Health Assembly abandoned the eradication strategy in 1969. A resurgence of malaria began at about that time and today reaches into areas where eradication or control had been achieved. A global malaria crisis looms. In 1993 the WHO adopted a Global Malaria Control Strategy that placed priority in control of disease rather than infection. This formalises a policy that emphasises diagnosis and treatment in a primary healthcare setting, while de-emphasising spraying of residual insecticides. The new policy explicitly stresses malaria in Africa, but expresses the intent to bring control programmes around the world into line with the strategy. This review raises the argument that a global control strategy conceived to address the extraordinary malaria situation in Africa may not be suitable elsewhere. The basis of argument lies in the accomplishments of the Global Eradication Campaign viewed in an historical and geographical context. Resurgent malaria accompanying declining vector control activities in Asia and the Americas suggests that the abandonment of residual spraying may be premature given the tools now at hand. The inadequacy of vector control as the primary instrument of malaria control in holoendemic Africa does not preclude its utility in Asia and the Americas.